HOW ADDITIVE MANUFACTURING MIGHT CHANGE SPARE PART BUSINESS : Future scenarios for Finnish high-tech companies - Kangas, Santeri (My University, 2019)
This master’s thesis identifies the possible effects which additive manufacturing might have on the spare part business in the future. A literature review is made on the topics spare part management, the current state of additive manufacturing and a combination of these two themes on how additive manufacturing can affect spare part management. Based on the made literature review is a theoretical framework created which identifies the spare part management process, what external factors could affect the adaptation of additive manufacturing into the spare part process and how this manufacturing method might improve the spare part process. The management of spare parts is divided into four phases creation, fabrication, distribution and prediction and additive manufacturing is seen able to possibly improve these three latter ones. The empirical data is gathered from Finnish high-tech organizations and based on the received answers three different scenarios are provided to show diverse possible outcomes how additive manufacturing might affect spare part business. The research provides findings that the main benefits of additive manufacturing are seen in decreasing inventory sizes, ensuring more accurate and faster lead times and more possibilities in the materials design phase.
Keywords: Additive manufacturing, spare part management, scenarios